Osthole Stimulated Neural Stem Cells Differentiation into Neurons in an Alzheimer's Disease Cell Model via Upregulation of MicroRNA-9 and Rescued the Functional Impairment of Hippocampal Neurons in APP/PS1 Transgenic Mice - Li, Shao-Heng; Gao, Peng; Wang, Li-Tong; Yan, Yu-Hui; Xia, Yang; Song, Jie; Li, Hong-Yan; Yang, Jing-Xian (Frontiers in Neuroscience, 2017)
Alzheimer's disease (AD) is the most serious neurodegenerative disease worldwide and is characterized by progressive cognitive impairment and multiple neurological changes, including neuronal loss in the brain. However, there are no available drugs to delay or cure this disease. Consequently, neuronal replacement therapy may be a strategy to treat AD. Osthole (Ost), a natural coumarin derivative, crosses the blood-brain barrier and exerts strong neuroprotective effects against AD in vitro and in vivo. Recently, microRNAs (miRNAs) have demonstrated a crucial role in pathological processes of AD, implying that targeting miRNAs could be a therapeutic approach to AD. In the present study, we investigated whether Ost could enhance cell viability and prevent cell death in amyloid precursor protein (APP)-expressing neural stem cells (NSCs) as well as promote APP-expressing NSCs differentiation into more neurons by upregulating microRNA (miR)-9 and inhibiting the Notch signaling pathway in vitro. In addition, Ost treatment in APP/PS1 double transgenic (Tg) mice markedly restored cognitive functions, reduced Aβ plague production and rescued functional impairment of hippocampal neurons. The results of the present study provides evidence of the neurogenesis effects and neurobiological mechanisms of Ost against AD, suggesting that Ost is a promising drug for treatment of AD or other neurodegenerative diseases.